SOUTH–SOUTH TRADE LIBERALISATION AS A WAY OF REDUCING THE IMPACT OF THE FINANCIAL CRISIS? AN EXPLORATORY CGE SIMULATION. (November 2013) - Mold, Andrew; Prizzon, Annalisa; Lawson, David; Amann, Edmund
Abstract Since 1990, South–South (S–S) trade has been growing much faster than overall world trade. The global financial crisis has, if anything, accentuated this trend, with S–S trade flows proving much more resilient than North–North flows. This has occurred despite the fact that developing countries still apply much higher tariffs to S–S trade than they do on trade with the North. On the basis of a computable general equilibrium model, we simulate reductions of tariff levels on S–S trade and find that the welfare gains are almost double those achievable through a similar reduction in applied tariffs between northern and southern countries. This suggests scope for instilling even more dynamism in S–S trade flows through further reduction of barriers to S–S trade. Copyright © 2013 John Wiley & Sons, Ltd.